A Cross Sectional Study on Scaling the Depression, Anxiety and Stress Level of Medical Students During COVID-19 in A Tertiary Level Medical Institution in India - Nath, Anamika; Ropmay, Amarantha Donna; Slong, Daunipaia; Patowary, Amar Jyoti; Ramu Damu, Dev Ashis; Jonpelly, Ankith; Shankar, Kishanth; Das, Prabal (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Social distancing, closure of institutions and lockdown has impacted the minds of all. Medical students are no exception to this. Objective: This study was taken up to find out the level of depression, anxiety and stress of medical students during COVID-19. Methods: It was a crosssectional study done at a tertiary institute for a period of one month in the middle of 2021. An online questionnaire, based on DASS 21 (Depression, Anxiety, and Stress Scale 21) scale, consisted of 7 questions each for each category viz. depression, anxiety and stress. While completing the DASS 21 questionnaire, each individual was required to indicate the presence of a symptom over the previous week. Chi-square test was used to analyze between the categorical variables. Results: Out of 183 study subjects, 16.39% had extremely severe depression, 13.66% extremely severe anxiety and 7.65% extremely severe stress. Development of anxiety with sex (p=0.04), and age (p=0.03), depression with age (p=0.02), development of depression with place of stay (p=0.04), and year of MBBS (p=0.0007) and anxiety with year of MBBS (p=0.0006) were found to be statistically significant. Conclusion: Development of depression, anxiety and stress in medical students must be recognized by the institution and measures for prevention like counselling facilities should be provided. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 161-167